Finding the sweet spot: optimizing criminal careers within the context of illicit enterprise - Gundur, Rajeev Vishwanath (Deviant behavior, 2020)
This article presents a framework for understanding three different strata within the context of illicit enterprise - being low hanging fruit, occupying the "sweet spot," and being the big enchilada. It shows that within each stratum, there is a progression of opportunity that contributes to criminal actors’ motivations to proceed with their criminal careers. Each progressing stratum has a significant barrier to entry that, once overcome, signals a state where risk, income potential, and stability change significantly. Nonetheless, illicit entrepreneurs continue to attempt to progress as long as they believe that opportunity is consistent, and the risk involved is acceptable. To that end, many criminal entrepreneurs who are successful in prolonging their criminal careers seek to occupy the "sweet spot," a position characterized by four outcomes: minimizing risk to reward, achieving low visibility, developing a comparative advantage in their illicit industry that, in turn, gives them independence, and economic stability.